Terjemahan Nama Instansi Pemerintah di Indonesia: Sebuah Tinjauan - Pamungkas, Muhammad Ersan Pamungkas (Kementerian Sekretariat Negara Republik Indonesia, 2023)
One type of translation tasks commonly carried out in many government institutions in Indonesia is translation of names of government institutions from Indonesian into foreign languages, notably English. This type of translation arguably poses not only technical challenges but also nontechnical challenges. This paper seeks to review challenges related to this type of translation. The research adopted a qualitative descriptive method by making an inventory of listing and presenting existing translations of the names of government institutions, proposing translations of the names of government institutions that are not yet available, and explaining problems identified in the existing translations, as well as problems related to the translation of the names of the government institutions. The result of this research shows that most government institutions do not have English translation of the names of their institutions. The existing translations of the names of several institutions even also differ in terms of translation style. To that end, it is important to not only encourage government institutions that do not have yet the official translations of their institutions to have them translated but also to harmonize the already existing translations in order to create uniformity of the translations of the names of all government institutions in Indonesia. Keywords: translation, government, names of institutions